أخلاقيات العمل : منظور إدارى معاصر فى تعزيز المسؤولية الإجتماعية للمنظمات : دراسة تحليلية لآراء العاملين فى مؤسسة الشاكرى للمبرات الاجتماعية - أحمد، جنان شهاب (جامعة القادسية - كلية الادارة والاقتصاد, 2013)
تفاعل متغيران لتشكيل الإطار النظري والتطبيقي لهذا البحث، وهما (أخلاقيات العمل والمسؤولية الاجتماعية) لكونهما من الموضوعات المهمة في البيئة العربية عامة، والبيئة العراقية خاصة، وقد انطلق البحث من مشكلة معبر عنها بعدد من التساؤلات الفكرية والتطبيقية في محاولة لبيان طبيعة ونوع العلاقة التي تربط بين هذين المتغيرين لدى العاملين في مؤسسة الشاكري للمبرات الاجتماعية البالغ عددهم (٥٧) فردا ضمن فروع (البياع ومدينة الصدر في بغداد، فرع النجف، فرع الناصرية، وفرع بعقوبة في ديالى). وتكمن أهمية البحث في أنه سيخرج بتأطير فكري لطبيعة متغيراته مستند إلى جهد تطبيقي لواقع أخلاقيات العمل في تعزيز المسؤولية الاجتماعية. ولتحقيق ذلك صيغت فرضيتان رئيستان اختبرت بمجموعة من الأدوات الإحصائية الوصفية والاستدلالية واستخدمت الاستبانة كأداة لجمع البيانات والمعلومات من المنظمة. وخرج البحث باستنتاجات شخصت حقيقة واقع المتغيرات في المنظمة المبحوثة كان أبرزها إيجابية في توافر متغيرات أخلاقيات العمل والمسؤولية الاجتماعية في المنظمة المبحوثة، إلا أن المتغير المستقل الفرعي (أخلاقيات القيادة) كان الأكثر تأثيرا في المتغير التابع (المسؤولية الاجتماعي)، مما يدل على أهمية السلوك الأخلاقي للقيادة وارتباطه بكل المتغيرات الأخرى في المنظمة. كما قدم البحث جملة من التوصيات كان أبرزها ضرورة توفير البنى التحتية اللازمة لأداء الشركات والمنظمات العراقية أعمالها وفق أخلاقيات العمل ومجال المسؤولية الاجتماعية، بالإضافة إلى وضع خطة متكاملة للثقافة التنظيمية التي يمكن أن تنتهجها المنظمة المبحوثة في تطبيق وممارسة أبعاد أخلاقيات العمل من جانب والمسؤولية الاجتماعية من جانب آخر. Two Variables interacted to form a theoretical and practical frame for this research, which are (business ethics and social responsibility) Because they are important issues in the Arab environment in general, and the Iraqi environment in special, this search started from a problem expressed by a number of questions of intellectual and applicative in an attempt to demonstrate the nature and type of the relationship between these two variables by workers at the institution shakiry for social charities reached (57) individuals within the branches of (Baya, and Sadr City in Baghdad, a branch of Najaf, Nasiriyah branch, and the branch of Baquba in Diyala). Important the search in intellectual framing for search \ variables depend on application afford for actuality of business ethics in corroborating social responsibility, In order to get this aim two main hypothesis has been formulated and tested with a set of descriptive statistical tools and a inferential, questionnaire was used as a tool to collect data and information from the organization. The search conducted to conclusions which determine variables actual in the organization, was most outstanding positive in the availability of variables business ethics and social responsibility in the search organization, but the independent variable (leadership ethics) are most influential in the dependent variable (social responsibility) which indicates the importance of ethical behavior for leadership and its association with all other variables in the Organization. It also presented research a number of recommendations was the most prominent need for the state to provide the infrastructure requisite to corporate performance and Iraqi organizations its accordance with business ethics and social responsibility as well as develop an integrated plan for organizational culture in the application and practice dimensions business ethics on the part of the social responsibility of the other side.
784107
Keywords: أخلاقيات العمل -- أخلاقيات العمل فى المنظمات -- الممارسات الأخلاقية للمنظمات -- المسؤولية الإجتماعية -- مؤسسة الشاكرى للمبرات الاجتماعية